Two new species of quill mites of the family Syringophilidae (Acariformes: Cheyletoidea) associated with treronine doves (Columbiformes: Columbidae: Treroninae) - Kaszewska, Katarzyna; Kavetska, Katarzyna; Skoracki, Maciej (Zootaxa, 2014)
Two new species of quill mites (Acariformes: Syringophilidae) associated with doves of the subfamily Treroninae (Columbiformes: Columbidae) from the Oceanian realm are described: Gunabopicobia masalaje sp. nov. from six avian host species, Ptilinopus iozonus Gray (type host) Ducula pistrinaria (Bonaparte), D. rosacea (Temminck), D. rufigaster (Quoy and Gaimard), D. spilorrhoa (Gray), D. luctuosa (Temminck), and Peristerophila lature sp. nov. also from six host species Ducula luctuosa (type host ), D. spilorrhoa, Ptilinopus jambu Gmelin, P. melanospilus Salvadori, P. porphyreus Temminck, P. regina Swainson. Additionally, Treron waalia (Meyer) is noted as a new host species for Meitingsunes columbicus Glowska and Skoracki, 2010.